2012
DOI: 10.1016/j.neurobiolaging.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in processing faces from detection to identification: ERP evidence

Abstract: We examined the ability of people 70 to 90 years old to apply global, configural and featural faceprocessing strategies. In addition we investigated age-related changes in the ability to categorize faces at basic, subordinate and individual levels. Using the N170 potential as index of early face processing and the P300 component as index of categorical decision making and effort, we found significant age-related perceptual changes which slowed and somewhat impaired face processing. Specifically, older particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
60
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 153 publications
18
60
2
Order By: Relevance
“…N170 amplitude also increased with participant age, replicating and extending previous reports for old (Daniel & Bentin, 2012;de Fockert. Ramchurn.…”
Section: Neural Correlates Of Aging In Face Recognition Memorysupporting
confidence: 88%
See 1 more Smart Citation
“…N170 amplitude also increased with participant age, replicating and extending previous reports for old (Daniel & Bentin, 2012;de Fockert. Ramchurn.…”
Section: Neural Correlates Of Aging In Face Recognition Memorysupporting
confidence: 88%
“…In a similar way, both N170 (Wiese et al, in press;Wiese, Schweinberger, & Hansen, 2008) and the vertex positive potential (VPP; Ebner, He, Fichtenholtz, McCarthy, & Johnson, 2011), which is assumed to be the frontocentral positive counterpart of N170 (Jeffreys, 1989;Joyce & Rossion, 2005), have been reported to be larger for old as compared with young faces. Finally, N170 has been observed to be delayed (Gazzaley et al, 2008;Rousselet et al, 2009;Wiese, Schweinberger, & Hansen, 2008) and increased (Daniel & Bentin, 2012;Gao et al, 2009;Rousselet et al, 2009) in older or middleaged (Chaby, George, Renault, & Fiori, 2003) relative to young participants. At some variance with these results, an earlier study by Pfütze, Sommer, and Schweinberger (2002) did not detect age-related changes in the N170.…”
Section: Event-related Potentialsmentioning
confidence: 97%
“…Similarly, some studies observed an enhanced N170 amplitude in older adults (Daniel & Bentin, 2012;Gao et al, 2009;Rousselet et al, 2009), while others did not . N170 amplitude differences have been suggested to reflect more effortful processing during early stages of face perception in older adults, which is also in line with the finding of smaller N170 inversion effects in this age group (e.g., Gao et al, 2009;Komes et al, 2015).…”
Section: Effects Of Cognitive Ageing In Face and Person Recognitionmentioning
confidence: 93%
“…Impedances were kept below 50 kX and the recording was initially referenced to the vertex electrode (Cz) before being converted to an average reference. In accordance with other studies examining the N170, we applied an offline bandpass filter of 0.5-30 Hz (Daniel & Bentin, 2010;Taylor, McCarthy, Saliba, & Degiovanni, 1999). Then the EEG was segmented into 600-ms epochs, time-locked to the auditory action cue (epochs extended from 100 ms prior to the tone to 500 ms after the tone).…”
Section: Eeg Recording and Analysismentioning
confidence: 99%